Catatan Awal Kongsi Tionghoa di Tanjungpinang Awal Abad ke-20 - Zulfa Saumia (Lembaran Sejarah, 2021)
This article aims to reveal the competition, power struggles and influence of the Chinese kongsi in the Tanjungpinang Chinese community in the 20th century. The research method used is the historical method through literature and archive studies by tracing sources in the form of books, government archives, magazines, and newspapers. The results of this study indicate that in Tanjungpinang there were various kongsis such as Tjaap Seng (arak), Eng Bie (tobacco) and Nan Yang (tobacco), Ngee Heng, Quan Teck Hoe, and Gagak Putih. Each kongsis in Tanjungpinang consists of various groups ranging from traders and coolies and has a base all the way to the countryside. Each of them has the same goal, namely control over territory and the economy. To achieve this goal, it is important to get help from local authorities which ends in conflicts like the one between Ngee Heng's kongsi and Quan Teck Hoe.